Rubber mill wastewater treatment using sequence batch Reactor in aerobic condition - Caesar Bidal Clement Peter, Caesar Bidal (2010)

(untitled)
A sequencing batch reactor (SBR) has certain advantages over conventional activated sludge processes (ASP) for the treatment of Rubber mill wastewater. The performance of a sequencing batch reactor in treating rubber mill wastewater effluents was investigated with a suspended biomass configuration and operating under aerobic conditions. Two reactors were used in this study with varying organic loading rates (OLR) and Hydraulic retention time (HRT). A total sequence of 24 h (15 min: filling phase; 23 h: reaction phase (aeration with recirculation); 30 min: setting; and 15 min: withdrawal) was employed and studied with various organic loading rates (0.047 kg COD/m3/day and 0.0933 kg COD/m3/day for reactor 1) and (0.1399 kg COD/m3/day and 0.1866 kg COD/m3/day for reactor 2). The SBR performance was assessed by means of Chemical oxygen demand (COD), Biochemical oxygen demand (BOD), Zinc, Nitrogen removal and operational parameters such as pH, sludge volume (SV), suspended solids (SS) and volatile suspended solids (VSS), which were monitored during the reactors operation. The SBR showed relatively more efficient performance in treating the rubber wastewater about 81.24% and 74.81% COD respectively was removed and 91% and 90% BOD respectively was removed. A final zinc concentration of 0.4 mg/L and 0.98 mg/L were achieved in reactor 1 and 2 respectively.